2015
DOI: 10.1007/s00284-015-0822-x
|View full text |Cite
|
Sign up to set email alerts
|

Catalase Enhances Growth and Biofilm Production of Mycoplasma pneumoniae

Abstract: Mycoplasma pneumoniae causes chronic respiratory disease in humans. Factors thought to be important for colonization include the ability of the mycoplasma to form a biofilm on epithelial surfaces and the production of hydrogen peroxide to damage host tissue. Almost all of the mycoplasmas, including M. pneumoniae, lack superoxide dismutase and catalase and a balance should exist between peroxide production and growth. We show here that the addition of catalase to cultures enhanced the formation of biofilms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Interestingly, a recent report suggested that inclusion of catalase in the culture medium can considerably increase the organism's rate of growth, possibly by destroying autoinhibitory hydrogen peroxide (278). However, it remains to be seen if this modification of established culture media will be validated by others and become widely adopted.…”
Section: Culturementioning
confidence: 99%
“…Interestingly, a recent report suggested that inclusion of catalase in the culture medium can considerably increase the organism's rate of growth, possibly by destroying autoinhibitory hydrogen peroxide (278). However, it remains to be seen if this modification of established culture media will be validated by others and become widely adopted.…”
Section: Culturementioning
confidence: 99%
“…Bacterial antioxidant activities have been shown to influence biofilm formation (Kim et al, 2006;Simmons and Dybvig, 2015;Tondo et al, 2016). To analyze the structural characteristics of the R. solanacearum biofilm, we generated Green Fluorescent Protein (GFP)-labeled strain derivatives (Table 1) and observed their growth development on chambered cover glass slides by confocal laser scanning microscopy over a 5-day period.…”
Section: Biofilm Formation Is Affected By the Deletion Of Katementioning
confidence: 99%
“…Whether these molecules are synthesized by the bacteria or pirated from the host (mycoplasmas do both), the role biofilms play in protecting the bacteria is critical. Several Mycoplasma species including Mycoplasma pneumoniae, a human pathogen, (Simmons et al, 2013;Simmons and Dybvig, 2015;Feng et al, 2018) and Mycoplasma pulmonis, a rodent pathogen, form biofilms in vitro and in vivo (Simmons and Dybvig, 2009). Similarly, Ureaplasma species have been shown to form biofilms in vitro, suggesting that the ability to form higher complexity bacterial structures is found across the class Mollicutes (Garcia-Castillo et al, 2008;Pandelidis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%